A case of thoraco-omphalopagus conjoined twins with intrauterine death - Khanam, Rosy; Choudhury, Shabir Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Conjoined twins or Siamese twins are identical twins that are joined in utero. The original Siamese twins were born in Siam (now Thailand) in 1811. They were males and lived for about 62 years. Incidence being 1 in 49,000 births to 1 in 1,89,000 births, this phenomenon is very rare. Approximate half are stillborn and one- third die within 24 hours of birth. Five types of conjoint twins are classically described, thoracopagus, omphalopagus, pygopagus, ischiopagus and craniopagus. With a reported incidence of 74-75% of all conjoint twins, Thoracopagus is the most common type. Omphalopagus with an incidence of 0.5% is the least common. Here we are reporting a case of thoraco-omphalopagus twin pregnancy with intra uterine death delivered by hysterotomy.